Phytoconstituents as emerging therapeutics for breast cancer: Mechanistic insights and clinical implications - Devaraji, Mahalakshmi; Thanikachalam, Punniyakoti V. (Cancer pathogenesis and therapy, 2025)
Breast cancer remains one of the leading causes of cancer-related morbidity and mortality among women worldwide, necessitating the development of novel therapeutic strategies. Phytoconstituents, naturally plant-derived bioactive compounds, have emerged as promising agents for breast cancer therapy due to their multifaceted mechanisms of action. This review examines the role of phytoconstituents in inducing apoptosis, inhibiting breast cancer cell proliferation, and suppressing metastasis. Furthermore, the anti-angiogenic effects of these compounds are discussed, highlighting their potential to disrupt tumor vascularization. We also summarize the in vitro and in vivo study-derived preclinical evidence supporting the efficacy of phytoconstituents. The synergistic potential of phytoconstituents with conventional therapies is also explored, emphasizing their ability to enhance treatment efficacy while minimizing adverse effects. We also address the challenges and limitations in the clinical application of phytoconstituents, paving the way for future research. This review provides insights into the therapeutic potential of phytoconstituents in breast cancer and their underlying mechanisms, advocating for their integration into existing treatment regimens. [Display omitted] •Phytoconstituents show multi-targeted mechanisms in breast cancer therapy.•They induce apoptosis, inhibit angiogenesis, and suppress metastasis.•Preclinical and clinical evidence supports their therapeutic potential.•Challenges with their use include bioavailability and clinical translation.•Should be studied in the areas of nanotechnology, personalized therapy, and synergism.